Size dependent oxygen buffering capacity of ceria nanocrystals - Xu, J; Harmer, J; Li, G; Chapman, T; Collier, P; Longworth, S; Tsang, S (2010)
The structural, chemical and electronic changes of ceria as a function of decreasing particle size have been studied: at sizes below 5 nm the total amount of reducible oxygen dramatically increases due to superoxide formation on the ceria surface, a result indicative of a size dependent oxygen buffering capacity. © The Royal Society of Chemistry 2010.